2022
DOI: 10.1186/s12887-022-03187-4
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian multilevel analysis of determinants of acute respiratory infection in children under the age of five years in Ethiopia

Abstract: Background Acute respiratory tract infection (ARI) is one of the leading causes of illness and mortality in children under the age of five worldwide. Pneumonia, which is caused by a respiratory tract infection, kills about 1.9 million children under the age of 5 years around the world. The majority of these deaths occur in underdeveloped countries. According to the 2016 Ethiopia Demographic and Health Survey (EDHS), the prevalence rate of ARI in Ethiopia was 7%. Prevalence is defined as the num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Among reviewed studies, 60.2% [18] and 1.9% [16] were the highest and lowest reported prevalence of ALRTIs, respectively. Furthermore, seven studies reported a prevalence between 1% and 10% [15][16][17][19][20][21][22]. The majority of the reviewed studies that provided the rates were between 11% and 20% [16, [23][24][25][26][27][28][29].…”
Section: Findings Prevalence Of Alrtis In Ssamentioning
confidence: 99%
See 3 more Smart Citations
“…Among reviewed studies, 60.2% [18] and 1.9% [16] were the highest and lowest reported prevalence of ALRTIs, respectively. Furthermore, seven studies reported a prevalence between 1% and 10% [15][16][17][19][20][21][22]. The majority of the reviewed studies that provided the rates were between 11% and 20% [16, [23][24][25][26][27][28][29].…”
Section: Findings Prevalence Of Alrtis In Ssamentioning
confidence: 99%
“…For instance, children under ve who are underweight [21,25] or stunted [25,41], and those anaemic [39] and not exclusively breastfed or poorly breastfed [1,15,21,37] are more likely to suffer ALRTIs. Unfortunately, unvaccinated children under ve [1] or children who did not complete their vaccination [13] or did not receive vitamin A supplements [19,20,39] are at higher risk of ALRTIs. Perhaps, children with existing health issues such as HIV [14] and a history of diarrhoea [19,20,23,25,28] become more vulnerable to ALRTIs (See Table 3 for details).…”
Section: Risk Factors Of Alrtis Of Children Under Ve In Ssamentioning
confidence: 99%
See 2 more Smart Citations
“…It risks young children, the elderly, and those with immune system disorders. Acute respiratory infections are thought to cause 2.6 million child deaths annually worldwide, according to the World Health Organization (WHO) [1]. Infections in children with human metapneumovirus (hMPV) and bocavirus (HBoV) are linked to a high prevalence of ARTIs.…”
mentioning
confidence: 99%